(untitled) - Food & Agriculture Organization of the United Nations (FAO) (Rome, 1987)
The publication describles the production, properties and main application of the three major phy-colloids extracted from seaweed: agar, alginate and carragenan,.....
Keywords: Marine algae,Tảo biển